HIV-associated lymphomas - G. A. Dudina; Ch. K. Mabudzada; A. A. Ogannisyan; V. N. Nemikin (Креативная хирургия и онкология)
A steady worldwide increase in the number of people living with HIV (PLHIV) and diagnostic methods requires a separate review of patient-specific nosologies, including lymphoproliferative diseases, some of which are directly associated with the virus due to its oncogenic effect and those that do not relate directly to HIV but introduce nuances to diagnostic and therapeutic approaches when a patient is HIV-positive. Towards this, the paper generally reviews lymphomas in PLHIV, presents the WHO classification of HIV-associated lymphomas, describes a contemporary view of the known mechanisms of pathogenesis, including the role of opportunistic infections, and general principles of diagnostic and therapeutic tactics, provides recommendations on modifying the doses of chemotherapy correlated with the immune status and on preventing CNS involvement. Specific types of lymphoma (Burkitt’s lymphoma, diff use large B-cell lymphoma) are considered separately, including those most frequently associated with patients living with HIV (primary effusion lymphoma, plasmablastic lymphoma, primary central nervous system lymphoma), but rare in the uninfected population.